Assessing the Effect of Direct Selling Strategies on Customer Loyalty in the Nigerian Commercial Banks - Solomon, Egbule A. C.; Stanley, Onobrakpeya Akpevwe; Ufuoma, Akpobire O.; Success, Obieze Ewere (Social Science Learning Education Journal, 2017)
The general objective of the study is to determine the effect of direct selling strategies on customer loyalty in the Nigerian banking industry. The cross sectional survey research design method was adopted. The sample objects were 226 staff of some selected commercial banks in Asaba, Delta State. A validated structured questionnaire was used to illicit responds from respondents. The multiple regression analysis was used as analytical tools for testing the hypotheses. The findings revealed that face-to-face communication, sales technology, sales team relationship commitment as components of direct selling strategies exhibited a significant positive impact on customer loyalty. The study therefore, recommends that competitive pressures to respond to the next generation and the growing use of technology among all age groups require the direct selling industry to find the right balance of high tech and high touch.